Improved Photometric Standards and Calibration Procedures at NIST - Ohno, Yoshihiro (J Res Natl Inst Stand Technol, 1997)
NIST has recently established a detector-based luminous intensity unit (candela, cd), which is derived from the NIST absolute cryogenic radiometer. Subsequently, the luminous flux unit (lumen, lm) and the luminance unit (cd/m(2)) have been established based on the detector-based candela, and now all the NIST photometric units are tied to the cryogenic radiometer. The illuminance unit is realized and maintained on five standard photometers. The large dynamic range of the standard photometers eliminates the need for maintaining many working standard lamps of various wattages. The luminous intensities of lamps are determined from the illuminances measured with these photometers and the distances measured with a linear encoder system. Transfer photometers and illuminance meters are calibrated by direct comparison with the standard photometers with no distance measurements involved. The luminous flux unit is realized using an absolute integrating sphere method newly developed at NIST. The luminance unit is realized on an integrating sphere source, which is used for calibration of other luminance sources and luminance meters. These detector-based methods have made it possible to reduce the uncertainties of photometric calibrations and to provide more varieties of photometric calibration services at NIST.